Characterisation of the transition type in optical band gap analysis of in-flame soot - Bauer, Florian; Bräuer, Phillipp; Aßmann, Simon; Thiele, Maximilian A.; Huber, Franz; Will, Stefan (Combustion and Flame, 2022)
Semiconductor materials are characterised by a band gap between conduction and valence band, which can either be of direct or indirect nature depending on the crystal momentum. In case of applying the so-called Tauc method to infer the band gap value, both transition types are described by different values for the transition type exponent. In the case of soot particles, the optical band gap is an important quantity during the evolution process to describe the optical characteristics mainly linked to the underlying structural properties. In this work, an approach to infer the optical band gap value together with the transition type exponent is used to shed light on the electronic nature and optical properties of soot during its formation process. In situ UV–Vis-NIR extinction measurements as well as ex situ Raman spectroscopy are performed in a non-premixed ethylene/air flame at two different positions in the flame reflecting different stages of the soot formation process. The results reveal two important tendencies: first, an increase in the band gap energy of young soot is observed, possibly caused by the curvature of initially planar polycyclic aromatic hydrocarbon monomers due to the presence of odd-numbered rings in the hexagonal aromatic lattice. Second, a decrease of the transition type exponent value can be observed, indicating a shift from an indirect transition to a more direct band structure. Further, the indirect band gap assumption for mature soot and its band gap value close to 0.2 eV can be confirmed experimentally. The Raman results provide additional insight in the atomic fine structure of the soot particles regarding the defect density and the loss of amorphous character with increasing maturity.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Raman spectroscopy; Soot band gap energy; Soot formation; Tauc method; Transition type